Literary translation universals: a psycholinguistic study of the novice translators' common choices - Zasiekin, Serhii V.; Засєкін, Сергій Васильович (Lesya Ukrainka Eastern European National University, 2014)
The paper outlines the study of translation S-universals and is based both on the psycholinguistic model of literary translation, which combines two approaches to language organization in today’s neuroscience – cognitivism and connectionism, and on the experimental data that demonstrate its validity. A free word association test was used to identify a translator’s cognitive style as a universal tendency determining his linguistic choice. This psycholinguistic tool helped explore the ways how the meaning of the original text was reconstructed in the target text by the selected group of novice translators. A quantitative content analysis and psycholinguistic text analysis were applied for the purpose of studying the correlation between specific textual features of authors and those of the translators. As the empirical study showed, the S-universals maintain the status of common strategies depending on translator’s cognitive style. A ‘think aloud protocol’ (TAP) analysis was used to explore the ways in which the meaning of the original text was reconstructed in the target text by the novice translators. A content analysis and psycholinguistic text analysis were applied for the purpose of studying the correlation between specific textual features of authors and those of translators. The results of the empirical study showed that the observed S-universals, while maintaining the status of common strategies, clearly depend on translator’s cognitive style (analytical or synthetic), and his dominant channel (visual, auditory, kinesthetic) of source text perception. Стаття висвітлює психолінгвістичний підхід до розуміння перекладацьких S- універсалій. Автор робить спробу продемонструвати їхню важливість та вплив на діяльність перекладача в контексті психолінгвістичної моделі художнього перекладу. Вона ґрунтується на двох парадишмах нейронауки – конекціонізмі та когнітивізмі. Вільний асоціативний експеримент має на меті встановити когнітивний стиль перекладачів. Конент-аналіз та психолінгвістичний аналіз сприяли встановленню кореляції текстових рис тексту оригіналу та перекладів. Процедура «думай вголос» застосована для виявлення того, як реконструюється значення вихідного тексту безпосередньо під час відтворення тексту перекладачами-новачками. Результати емпіричного дослідження показали, набір S-універсалій як спільних стратегій перекладачів залежить від їхнього когнітивного стилю – аналітичного чи интетичного, а також їхньої провідної модальності – аудіальної, візуальної, тактильної.
Універсалії в художньому перекладі: психолінгвістичне дослідження спільних рішень перекладачів-новачків
Keywords: translation; psycholinguistic model; translation universal; translator’s cognitive style; dominant channel of perception; переклад; психолінгвістичні модель; перекладацька універсалія; когнітивний стиль; провідний канал сприйняття інформації